Die betekenis van H.G. Stoker se filosofie vir die teologie - Heyns, Johan Adam (Koers, 1994)
The presupposition from which this article proceeds is the sincere conviction that the philosophy of H.G. Stoker has a significant value for the Reformed theology although this has not as yet been fully exploited. On the contrary - severe criticism, even from within certain circles in Reformed theology, has been launched against Stoker's views. To illustrate the relevancy of Stoker’s philosophy for Reformed theology. I do not deem it necessary to expound his views extensively, but will concentrate only on a few but important and fundamental aspects. In this regard the following aspects are emphasized: the fundamental and indispensable role Scripture plays as a source of knowledge also for theoretical scientific activities; the radical distinction between God and cosmos; by God’s power and sovereignty He gives - through his Word - order and structure to the world and continually imparts existence to his creatures; God's purposes in his work of creation are the basis for all value; in God’s good creation evil has intruded but this is not God’s doing; created in the image of God, man is free and responsible and mandated to rule the earth in obedience to God. The theological implications of these views can be expressed comprehensively in the Biblical concept of the kingdom of God. In conclusion the concept of the kingdom is cursorily examined.